2020
DOI: 10.1093/jamia/ocaa221
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in self-reported telehealth use during the COVID-19 pandemic: a secondary analysis of a US survey of internet users from late March

Abstract: Objective Widespread technological changes, like the rapid uptake of telehealth in the U.S. during the COVID-19 pandemic, risk creating or widening racial/ethnic disparities. We conducted a secondary analysis of a cross-sectional, nationally representative survey of Internet users to evaluate whether there were racial/ethnic disparities in self-reported telehealth use early in the pandemic. Materials and Methods The Pew Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(128 citation statements)
references
References 30 publications
10
108
5
Order By: Relevance
“…With the seriousness of the pandemic, preferences for a psychiatric visit type based on sex may have had less impact; this may also be true for race. Compared to other studies [16,21], our sample revealed no divide in selection of visit type with regard to patient race. This may stem from our cohort being predominantly White.…”
Section: Xsl • Focontrasting
confidence: 57%
“…With the seriousness of the pandemic, preferences for a psychiatric visit type based on sex may have had less impact; this may also be true for race. Compared to other studies [16,21], our sample revealed no divide in selection of visit type with regard to patient race. This may stem from our cohort being predominantly White.…”
Section: Xsl • Focontrasting
confidence: 57%
“…Some initiatives have also been based on the development of surveys to thoroughly analyze the causes of the Digital Divide [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The racial and ethnic differences in the areas of remote assistance during the COVID-19 pandemic [ 17 ].…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…2 Finally, though over 90% of the population is White, most racial and ethnic groups are represented, including the American Indian Nations and tribal communities of Wisconsin. 19 Previous studies presented changes in the scale and applications of telemedicine use during the first wave of the pandemic, which occurred around March to May of 2020, [20][21][22][23][24][25] as well as the utility of telemedicine in treating cases of suspected COVID-19. 24,26,27 Few studies thus far have examined telemedicine utilization patterns after May 2020, as outpatient telemedicine delivery grew more widespread.…”
Section: Background and Significancementioning
confidence: 99%